Studi Pustaka : Ekstraksi dan Potensi Utilitasasi Ekstrak Komponen Bioaktif Tanaman Murbei di Indonesia - Yuyun Yuniati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Mulberry is one of the plants that grows well in Indonesia, and has been used to support daily economic activities. Mulberries are of interest to researchers as research objects, regarding the bioactivity of mulberry plants. Over the past decade, from 2013 to 2023, research has been carried out regarding mulberries in Indonesia, with the aim of extracting and analyzing the extract substances. Data from 12 local research journals is known regarding the use of mulberry roots, stems and leaves to be extracted and applied for compound identification purposes, a study of the extraction methods used, and the specific purpose of mulberry extract as a preservative, patch formulation material, as well as an antibacterial agent, preservative, and antioxidants. The mulberry extraction procedures used are the maceration method, wave-based extraction (microwave and ultrasonic) and water bath energy. Qualitative analysis testing of mulberry extract substances was carried out to determine the content of alkaloids, tannins and terpenoid compounds. Quantitative analysis testing of mulberry extract substances was carried out to measure antioxidant activity, anthocyanin levels, and the biological activity of mulberry extract substances.